Emphysematous cholecystitis presenting as gas-forming liver abscess and pneumoperitoneum in a dialysis patient: a case report and review of the literature. Issue 1 (December 2016) - Liao, Chen-Yi; Tsai, Chi-chang; Kuo, Wu-Hsien; Ben, Ren-Jy; Lin, Ho-Cheng; Lee, Ching-Chang; Su, Kuan-Jen; Wang, Han-En; Wang, Chih-Chiang; Chen, I-Hung; Chien, Shang-Tao; Tsai, Ming-Kai
Abstract Background Emphysematous cholecystitis is a rare variant of acute cholecystitis with a high mortality rate. The combination of emphysematous cholecystitis, liver abscess and pneumoperitoneum are even rarer. Herein we present a case of emphysematous cholecystitis in a senile diabetic lady who had worsening hemodynamics while undergoing hemodialysis. Case presentation A 64-year-old woman with history of type 2 diabetes mellitus and end stage renal disease with regular hemodialysis presented to the emergency department with a 1-day history of sudden onset of lassitude and hypotension during hemodialysis. The result of a computed tomography (CT)-scan revealed air encircling the gallbladder, liver parenchymal and minimal pneumoperitoneal and liver abscess with no cholelithiasis. The patient had received empirical antibiotics with piperacillin-tazobactam 2.25 g intravenous route every 6 h for 14 days and cholecystectomy with surgical debridement and lead an uneventful postoperative hospital course. Escherichia coli was demonstrated as well as blood culture and peritoneal fluid culture. Conclusion In a senile diabetic and dialysis patient, we should take emphysematous cholecystitis into consideration once vague abdominal pain occurrs. Empirical antibiotic therapy and adequate surgical intervention should take place as soon as possible.